2017
DOI: 10.1261/rna.059519.116
|View full text |Cite
|
Sign up to set email alerts
|

A complex of Arabidopsis DRB proteins can impair dsRNA processing

Abstract: Small RNAs play an important role in regulating gene expression through transcriptional and post-transcriptional gene silencing. Biogenesis of small RNAs from longer double-stranded (ds) RNA requires the activity of dicer-like ribonucleases (DCLs), which in plants are aided by dsRNA binding proteins (DRBs). To gain insight into this pathway in the model plant , we searched for interactors of DRB4 by immunoprecipitation followed by mass spectrometry-based fingerprinting and discovered DRB7.1. This interaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 83 publications
(138 reference statements)
3
18
0
Order By: Relevance
“…Perfect co-localization most likely reflects the direct association of DRB2 and DRB4 on replicating dsRNA within the VRCs. This result is in line with the experimentally verified ability of DRB2 and DRB4 to bind dsRNA [36, 50] and of DRB4 to bind TYMV dsRNA in vivo [41]. DRB2 was recently shown in A. thaliana to re-localize to cytoplasmic punctate bodies upon infection by TuMV, TSWV and TYMV [8] and DRB4 to re-localize from nuclei to cytoplasmic VRCs upon TYMV infection [41].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Perfect co-localization most likely reflects the direct association of DRB2 and DRB4 on replicating dsRNA within the VRCs. This result is in line with the experimentally verified ability of DRB2 and DRB4 to bind dsRNA [36, 50] and of DRB4 to bind TYMV dsRNA in vivo [41]. DRB2 was recently shown in A. thaliana to re-localize to cytoplasmic punctate bodies upon infection by TuMV, TSWV and TYMV [8] and DRB4 to re-localize from nuclei to cytoplasmic VRCs upon TYMV infection [41].…”
Section: Discussionsupporting
confidence: 77%
“…Despite showing low spectral counts in our IPs, two DRBs were identified in our analysis: DRB2 (AT2G28380, total counts: 4, Figure 4A ) and DRB4 (AT3G62800, total counts: 5, Figure 4A ) that were obvious candidates to test ( Figure 4 ). DRB2 was recently shown to localize to the replication complexes of different RNA viruses [8], to be able to bind dsRNA [36] and to play a role in endogenous small RNA biogenesis [32, 37, 38]. In non-infected plants DRB2:tRFP and B2:GFP localized to rather distinct cytoplasmic and nuclear structures, whereas a near-perfect colocalization of DRB2:tRFP and B2:GFP was observed in the VRCs upon TRV-PDS infection ( Figure 4B ), which was particularly evident at high magnification ( Figure 4C) .…”
Section: Resultsmentioning
confidence: 99%
“…29 However, the recent identification of a new clade of DRB protein (named DRB7), conserved in all vascular plants, 30 and the characterization of their implication in the formation of specific DRB complexes that selectively regulate the processing of endoIR-siRNA precursors, strongly suggest that endogenous IRs might be bona fide regulators of gene expression. 31,32 Members of the DRB7 family (DRB7.1 and DRB7.2), as opposed to the previously characterized DRB1-5, harbour a single dsRBM. 30 Genome-wide small RNA profiling and northern blot analysis performed on drb7.2 mutant plants revealed that lack of DRB7.2 does not significantly impact the accumulation of p4-siRNAs, miRNAs and tasiRNAs but strongly alters the production of endoIR-siRNAs.…”
mentioning
confidence: 99%
“…Indeed, whereas DCL2 and DCL3 have been shown to be purely located in the nucleus, DCL4 was shown to be mostly cytoplasmic. 31,32 By accumulating in the same subcellular compartment where endogenous IRs transcripts are produced, folded in dsRNA and, at least in a certain proportion, sequestered by the nuclear DRB4/DRB7.2 complex, the endoIR-siRNA precursors released in drb4 or drb7.2 mutant plants will be preferentially attacked by DCL3 and DCL2 over DCL4. In parallel, the apparent higher efficiency of DCL3 over DCL2 in processing these released substrates might possibly reflect differences in terms of steady-state level, affinity or activity of these 2 proteins, leading to DCL2 being outcompeted by DCL3.…”
mentioning
confidence: 99%
See 1 more Smart Citation